Concise informed consent to increase data and biospecimen access may accelerate innovative Alzheimer's disease treatments. Issue 4 (1st September 2017) - Hake, Ann M.; Dacks, Penny A.; Arnerić, Stephen P.; ,
Abstract: Introduction: Informed consent forms that restrict the distribution of data and samples have been an impediment to advancing Alzheimer's disease (AD) understandings and treatments. The Coalition Against Major Disease public‐private partnership developed concise addenda to responsibly broaden data access of informed consent forms. Methods: Coalition Against Major Disease members identified key elements for ensuring data and biospecimen access, and patient privacy protection according to applicable US law. Collaboration with the Alzheimer's Association established the understandability and relevance of the addenda with AD patients and Care Partners. Results: Two key findings are (1) patients with dementia and Care Partners were shocked that their data and samples are not broadly shared and (2) with diverse feedback, two concise addenda were created to enable data and sample sharing both within and outside future sponsored studies (see Boxes). Discussion: Increasing the access of valuable anonymized patient‐level clinical trial data has the potential to inform the foundational and regulatory science required to deliver innovative treatments for AD.